2023
DOI: 10.1227/neu.0000000000002555
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Prone Transpsoas Lateral Lumbar Interbody Fusion for Degenerative Lumbar Spine Disease: A Multicenter Study

Abstract: BACKGROUND AND OBJECTIVES: The prone transpsoas (PTP) approach for lateral lumbar interbody fusion (LLIF) is a novel technique for degenerative lumbar spine disease. However, there is a paucity of information in the literature on the complications of this procedure, with all published data consisting of small samples. We aimed to report the intraoperative and postoperative complications of PTP in the largest study to date. METHODS: A retrospective elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Authors cite inconsistent reporting standards for this wide range, stating that many authors of the included studies view transient neurologic symptoms as side-effects of required psoas manipulation rather than a true complication. Comparatively, in a 365 PTP-patient retrospective study by Soliman et al, the authors showed that prone lateral fusion resulted in new onset radiculopathy or lower-extremity sensory symptoms in only 8.2% of patients [51]. Farber et al and Patel et al reported similarly low rates of new onset of thigh neuropraxia among their PTP cohorts, at 13.3% and 11.9% respectively [46,50].…”
Section: Neuropathymentioning
confidence: 95%
See 4 more Smart Citations
“…Authors cite inconsistent reporting standards for this wide range, stating that many authors of the included studies view transient neurologic symptoms as side-effects of required psoas manipulation rather than a true complication. Comparatively, in a 365 PTP-patient retrospective study by Soliman et al, the authors showed that prone lateral fusion resulted in new onset radiculopathy or lower-extremity sensory symptoms in only 8.2% of patients [51]. Farber et al and Patel et al reported similarly low rates of new onset of thigh neuropraxia among their PTP cohorts, at 13.3% and 11.9% respectively [46,50].…”
Section: Neuropathymentioning
confidence: 95%
“…In the aforementioned lateral-decubitus meta-analysis by Hijji et al, the rate of inadvertent anterior longitudinal ligament (ALL) release was reported to be 2.9% [5]. Similarly, in their PTP cohort, Soliman et al reported an ALL rupture incidence of 2.2%, totaling 8 of the 365 patients [51]. Farber et al (5, 2.3%) and Buckland et al (3, 1.2%) describe similar rates of ALL release in their PTP cohorts [13,50].…”
Section: Inadvertent Anterior Longitudinal Ligament Releasementioning
confidence: 98%
See 3 more Smart Citations